The Association of CYP19A1 Variation with Circulating Estradiol and Aromatase Inhibitor Outcome: Can CYP19A1 Variants Be Used to Predict Treatment Efficacy? - Glubb, Dylan M.; O'Mara, Tracy A.; Shamsani, Jannah; Spurdle, Amanda B. (Frontiers in Pharmacology, 2017)
After menopause, estradiol is primarily synthesized in peripheral tissues by the enzyme aromatase, encoded by CYP19A1. CYP19A1 variation has been found to associate with circulating estradiol in postmenopausal women and this variation is best represented by the intronic variant rs727479. Estradiol plays an important role in the development of breast and endometrial cancer and aromatase inhibitor (AI) drugs are used in the treatment of both diseases. Responses to AIs, however, are variable and there is currently no way to identify patients who are more likely to receive a clinical benefit although multiple studies have proposed that genetic variation in CYP19A1 will have effects on AI efficacy. After review of the literature, we identified only eight candidate variant studies of sample size greater than 50 that describe associations CYP19A1 variation and the outcome of patients treated with AIs. Nominally significant associations with patient outcome were reported for several variants, including rs727479. However, only an association between rs4646 and time to progression was replicated in an independent study. Moreover, rs4646 is also the only variant that has an association with patient outcome that passes a multiple testing threshold and this variant is in linkage disequilibrium with rs727479, supporting the hypothesis that associations with patient outcome may be driven through the effects on circulating estradiol. Despite this preliminary evidence, well phenotyped and comprehensively genotyped patient sets, such as those from the Breast Cancer Association Consortium, need to be studied before conclusions can be drawn about the effects of CYP19A1 variation on AI efficacy.